PENERAPAN PENDEKATAN KONTEKSTUAL MENGGUNAKAN MEDIA GAMBAR UNTUK MENINGKATKAN KETERAMPILAN MENULIS DESKRIPSI PADA SISWA KELAS II SEKOLAH DASAR - Darmatul Asma Toja (Prima Magistra: Jurnal Ilmiah Kependidikan, 2020)
This research was conducted because it was found that there were problems in the Indonesian language subject for grade II students of Bhoanawa 2 Impres Elementary School which showed very low Indonesian learning outcomes. The formulations of the problems in this study are: 1) Does learning through a contextual approach by utilizing animal image media can improve writing writing skills ?; 2) Can a contextual approach using animal pictures media increase student activity? The data collection methods used were: observation, interview, test and documentation. The subjects in this study were all students in grade II of the Bhoanawa 2 Impres Elementary School, totaling 17 people. This type of research is Classroom Action Research. The results showed that the increase in writing skills in writing was 29%, or only 5 out of 17 students who were able to write well, which could achieve a greater value of 67. The results of cycle I increased to 47.05% (less) because of 17 students 8 students who managed to get a score above the value of the Minimum Completeness Criteria, and in cycle II an increase of 88.23% (very good), of the 17 students sampled there were 5 students in the very good category and 10 students in the good category.